G392 Tablets or liquids for children: who decides and why?. (7th April 2014) - Batchelor, HK; Marriott, JF; Venables, RH; Hodson, J; Stirling, HF
Abstract : Aims: This study investigated the opinions of healthcare professionals, specialist paediatric consultants, nurses, and pharmacists as well as general practitioners (GPs) regarding the age at which they would prescribe, supply or administer a solid dosage form to a child in order to understand if age significantly influenced formulation choice between healthcare professional groups. Materials and methods: A mixed methods (quantitative and qualitative) questionnaire was distributed to 97 healthcare professionals. This included paediatric: consultants (n = 17), hospital doctors (n = 27), pharmacists (n = 16), nurses (n = 9) and also GPs (n = 28) during routine CPD training sessions at University Hospitals Coventry and Warwickshire and Birmingham Children's Hospital. Statistical analysis was conducted using IBM SPSS 20. Statistical tests conducted were an ANOVA, followed by Tukey's HSD post-hoc test. Results: The age at which tablets were considered to be appropriate for use in children was lower amongst the specialist paediatric healthcare professionals (median ages were 7.5 years for consultants; 9 years for nurses; 8 years for pharmacists) compared to GPs (median age 12 years). Statistical analysis demonstrated differences between the age at which tablets would first be used as reported by different healthcare professionals (p = 0.001). Significant differences were detected between mean values reported by GPs and pharmacists (p = 0.012) and also GPs and paediatric consultants (p = 0.006). The age at which GPs first use tablets was higher than that reported by pharmacists and paediatric consultants as shown in Figure 1 . Conclusions: There is an educational need for GPs to understand the cost and practical implications associated with liquid formulations where tablets may be an acceptable and readily available alternative. This is particularly relevant where liquids are supplied as Specials which are associated with a higher costs yet inferior quality compared to licensed products supplied as tablets; a switch to tablet is better both economically and for the patient in many cases. Communication between specialist paediatric healthcare professionals and those in primary care settings needs to be optimised regarding the use of tablet formulations in younger children.